2021
DOI: 10.1186/s13046-021-01970-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived tumor models: a more suitable tool for pre-clinical studies in colorectal cancer

Abstract: Colorectal cancer (CRC), despite the advances in screening and surveillance, remains the second most common cause of cancer death worldwide. The biological inadequacy of pre-clinical models to fully recapitulate the multifactorial etiology and the complexity of tumor microenvironment and human CRC’s genetic heterogeneity has limited cancer treatment development. This has led to the development of Patient-derived models able to phenocopy as much as possible the original inter- and intra-tumor heterogeneity of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 188 publications
(272 reference statements)
1
36
0
Order By: Relevance
“…Among digestive cancers, colorectal cancer (CRC) represents the third most common cancer world-wide and the third highest cause of cancer-related mortality, which is responsible of about 10% of total cancer death [ 26 ]. CRC development resulted from the transformation of normal epithelium to adenoma and then adenocarcinoma.…”
Section: Orexins and Digestive Cancersmentioning
confidence: 99%
“…Among digestive cancers, colorectal cancer (CRC) represents the third most common cancer world-wide and the third highest cause of cancer-related mortality, which is responsible of about 10% of total cancer death [ 26 ]. CRC development resulted from the transformation of normal epithelium to adenoma and then adenocarcinoma.…”
Section: Orexins and Digestive Cancersmentioning
confidence: 99%
“…However, PDX models are promising tools for translational research. PDX models have been used for various types of cancer research such as drug evaluation, precision oncology, biomarker detection for drug sensitivity or resistance, and comprehension of tumor behavior [16,17,80,81]. For example, Berotti et al found that amplification of the Erb-B2 receptor tyrosine kinase 2 (ERBB2) gene is a determinant of driver of cetuximab resistance and predicts the response to epidermal growth factor receptor (EGFR) and HER-2-targeted therapies in a colon cancer PDX model [3].…”
Section: Translational Applications Of Pdx Modelsmentioning
confidence: 99%
“…A large PDX cohort could cover almost every stage and grade of histological subtype. Furthermore, clinical information, such as prognosis and drug sensitivity, can also be recorded [14][15][16][17]. Briefly, all materials and information from cancer patients and PDX models are stored in biobanks and data banks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, the patient’s tumor is mechanically and/or enzymatically treated, and then, the cells are incorporated into Matrigel to generate a 3D model. The PDOs can be maintained in culture and/or can be injected into immunocompromised mice [ 73 ]. These models are gaining presence in molecular oncology studies, particularly in the case of solid tumors, and may constitute an ex vivo 3D model closer to the tumor environment.…”
Section: Preclinical Models Of Adc Resistancementioning
confidence: 99%